1993
DOI: 10.1016/0014-5793(93)81754-n
|View full text |Cite
|
Sign up to set email alerts
|

A study of branched‐chain amino acid aminotransferase and isolation of mutations affecting the catabolism of branched‐chain amino acids in Saccharomyces cerevisiae

Abstract: The specific activity of branched-chain amino acid aminotransferase was highest when S. cerevltiue was grown in minimal medium containing a branched-chain amino acid as nitrogen source. Growth in complex media with glycerol or ethanol gave moderately high levels, whereas with glucose and fructose the specific activity was very low. Mutagenesis defined three genes (BAA1 to BAA3) required for branched-chain amino acid catabolism.The haul mutation reduced the specific activity of the aminotransferase, the station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…Growth in the presence of fusel alcohols such as isoamyl alcohol (derived from leucine) induces pseudohyphal growth (9,33). These pronounced morphological modifications are accompanied by an increase in the specific activity of succinate dehydrogenase and an increase of the chitin content (33).…”
Section: Fusel Alcohols and Acids As Signal Molecules: Role Of The Ehmentioning
confidence: 99%
“…Growth in the presence of fusel alcohols such as isoamyl alcohol (derived from leucine) induces pseudohyphal growth (9,33). These pronounced morphological modifications are accompanied by an increase in the specific activity of succinate dehydrogenase and an increase of the chitin content (33).…”
Section: Fusel Alcohols and Acids As Signal Molecules: Role Of The Ehmentioning
confidence: 99%
“…In S. cerevisiae, the first two steps of branchedchain amino acid catabolism are similar to those in other eukaryotes in that they involve first an aminotransferase and then 2-oxoacid dehydrogenase (Dickinson & Norte, 1993;Dickinson & Dawes, 1992). However, in yeast, major products of branched-chain amino acid catabolism are the so-called 'fusel' alcohols (Webb & 1963).…”
Section: Resultsmentioning
confidence: 99%
“…Some metabolic schemes even envisage a blending of catabolic and biosynthetic pathways (8). These and other considerations have led us to undertake a thorough re-examination of the catabolism of the branched-chain amino acids in S. cerevisiae which has confirmed that the first step is transamination (9). Two distinct aminotransferases have been shown to function both in amino acid biosynthesis and catabolism.…”
mentioning
confidence: 99%